2020
DOI: 10.11152/mu-2521
|View full text |Cite
|
Sign up to set email alerts
|

Various aspects of Contrast-enhanced Ultrasonography in splenic lesions – a pictorial essay

Abstract: Spleen pathology is rare in comparison with other abdominal organs, but often its lesions occur in complex pathological contexts, with systemic involvement. Although the lesions could be discretely symptomatic, their evolutionary potential might be severe. Conventional B-mode and Doppler ultrasound are the first-line imaging methods in spleen assessment, but frequently they do not allow the characterization of focal splenic abnormalities. Contrast-enhanced ultrasound (CEUS) is fast, safe, easy to perform, non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
1
4
1
Order By: Relevance
“…However, CEUS demonstrated that the former patient presented with rim-like enhancement that was maintained during the intermediate parenchymal phase, followed by slow wash-out in the late parenchymal phase; the latter patient showed non-enhancement in all phases. These were inconsistent with the findings from the study by Ioanitescu et al, which showed the malignant splenic lesions like splenic metastases and splenic lymphoma had rapid wash-out [ 24 ]. Therefore, malignant lesions were not considered for these 2 cases, and the 2 cases were finally confirmed by biopsy to be splenic TB.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…However, CEUS demonstrated that the former patient presented with rim-like enhancement that was maintained during the intermediate parenchymal phase, followed by slow wash-out in the late parenchymal phase; the latter patient showed non-enhancement in all phases. These were inconsistent with the findings from the study by Ioanitescu et al, which showed the malignant splenic lesions like splenic metastases and splenic lymphoma had rapid wash-out [ 24 ]. Therefore, malignant lesions were not considered for these 2 cases, and the 2 cases were finally confirmed by biopsy to be splenic TB.…”
Section: Discussioncontrasting
confidence: 96%
“…In our study, conventional US showed 1 patient with only 3 lesions, whereas 5 lesions with clearer borders were detected by CEUS. Thus, CEUS can be helpful for increasing the lesion detection rate, which is in agreement with the results of Ioanitescu et al [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…Although malignant splenic lesions are relatively rare in human medicine [ 17 , 84 , 85 , 86 ], in recent years, the importance of correctly diagnosing malignant lesions [ 84 , 87 , 88 , 89 , 90 ], together with the risk of hemorrhage, immune system impairment, and sepsis associated with invasive procedures [ 84 , 89 ] has propelled research into the use of contrast-enhanced ultrasonography to differentiate between malignant and benign lesions in human medicine [ 69 , 88 , 91 ]. In veterinary medicine, neoplastic splenic lesions are much more common [ 92 , 93 ] and not easily differentiated from benign processes through normal imaging techniques [ 75 , 76 , 77 ].…”
Section: Ceus-detected Spleen Abnormalities In Dogs and Catsmentioning
confidence: 99%
“…In human medicine, studies have shown that the use of CEUS does allow for the identification of malignant vs. benign splenic lesions, the former showing hypo-enhancement in the parenchymal phase independently of the enhancement in the arterial phase, with a faster wash-out rate compared to the surrounding normal splenic tissue [ 17 , 68 , 103 , 104 , 105 , 106 ]. In veterinary medicine, besides there being a greater range of histopathological changes in the spleen, they are more frequently found than in human medicine [ 91 , 92 , 93 ]. This has resulted in the study of a wider variety of neoplastic lesions and their CEUS characteristics.…”
Section: Ceus-detected Spleen Abnormalities In Dogs and Catsmentioning
confidence: 99%
“…A clear diagnosis regarding focal splenic lesions is difficult to achieve by imaging means, particularly due to imaging similarities and the scarcity of particular lesions [4][5][6]. Ultrasonography is the first step in diagnosis and evaluation of splenic tumors, and contrast-enhanced ultrasonography (CEUS) can add important information regarding the characteristics of focal splenic lesions [7].…”
Section: Introductionmentioning
confidence: 99%